Susceptibility of Mouse Brain to MCMV Infection and Neuroinflammation During Ontogeny - Fran Krstanović; Andrea Mihalić; Lucija Šakota; Berislav Lisnić; Stipan Jonjić; Ilija Brizić (Pathogens)
Human cytomegalovirus (HCMV) rarely infects the brain following infection of adult individuals. However, the virus readily infects the brain during congenital HCMV (cHCMV) infection, frequently causing severe neurodevelopmental and neurological sequelae. Interestingly, although the incidence of cHCMV infection is 0.5–1%, the proportion of congenitally infected individuals in which the virus manages to gain access to the brain is unknown. In this study, we used infection of mice with mouse cytomegalovirus (MCMV), the most commonly used experimental system for modeling HCMV disease in humans, to determine the impact of age on the susceptibility of the brain to cytomegalovirus infection and infection-mediated neuroinflammation. We demonstrate that infection of mice during various stages of neonatal development can lead to CMV neuroinvasion and inflammation. In contrast, MCMV infection does not result in MCMV neuroinvasion and neuroinflammation in weanling and adult mice. The obtained results establish a basis for elucidating the mechanisms of CMV neuroinvasion and the deleterious inflammatory response during ontogeny.